Near-infrared photodynamic chemiluminescent probes for cancer therapy and metastasis detection - Huang, Jingsheng (2023)
There is growing interest in the development of chemiluminescence (CL) probes for phototheranostics because of their minimized tissue autofluorescence. However, due to a lack of near-infrared (NIR)-absorbing chemiluminophores, current probes for NIR CL-guided phototherapy are based on nanoparticles made up of multiple components. We report bright unimolecular chemiluminophores with NIR absorptions and emissions, long CL half-lives and ideal photodynamic efficiency. One luminophore is modified into an activatable probe, DBPOL , with a turn-on CL signal and photodynamic activity that are specific to a cancer biomarker. The highly sensitive DBPOL allows CL-guided photodynamic therapy which completely inhibits tumor growth and lung metastasis in mouse models, and can be applied for noninvasive monitoring of lung metastasis. We provide molecular guidelines for NIR-absorbing CL probes for imaging-guided phototherapy.